Comparing Iranian and Spanish Electricity Markets with Nonlinear Time Series - Nasrazadani, Hajar; Muñoz Gracia, Maria Pilar (International Journal of Energy Economics and Policy, 2017)
Electricity market analysis is useful for accessing strategic market information in order to set energy policy. According to recent interpretations of the Article 44 of the Iranian Laws, the Iranian electricity market is to become a free market. Mechanisms that were implemented in the Spanish electricity market - a free market - provide a versatile benchmark to employ time series modeling approach to compare Iran and Spain’s electricity markets via price and load time series as two main indices. Here, we develop linear (ARMIA), heteroskedastic (ARMA-GARCH), and nonlinear time series models to model the Iranian/Spanish electricity market for price and load time series indices. We further utilize the conditional variance to propose the ARMA-TGARCH model as the best suited model for the Iranian electricity market price. We employ our models and time series analysis to forecast and question the status of the Iranian market structure as a free market. Keywords: Time series, forecasting, elecricity market, Spain, Iran JEL Classifications: C31, Q41, Q47